2001
DOI: 10.1099/0022-1317-82-7-1713
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a protective response in swine vaccinated with DNA encoding foot-and-mouth disease virus empty capsid proteins and the 3D RNA polymerase

Abstract: This work focuses on the development of a potential recombinant DNA vaccine against foot-andmouth disease virus (FMDV). Such a vaccine would have significant advantages over the conventional inactivated virus vaccine, in particular having none of the risks associated with the high security requirements for working with live virus. The principal aim of this strategy was to stimulate an antibody response to native, neutralizing epitopes of empty FMDV capsids generated in vivo. Thus, a plasmid (pcDNA3.1/P1-2A3C3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…One approach utilized a DNA inoculationbased strategy designed to produce empty capsids in inoculated animals (46,52,91,95). Similar studies using cDNA that encodes the entire viral genome but contains a mutation at the cell binding site were also performed (46,471).…”
Section: Disease Controlmentioning
confidence: 99%
“…One approach utilized a DNA inoculationbased strategy designed to produce empty capsids in inoculated animals (46,52,91,95). Similar studies using cDNA that encodes the entire viral genome but contains a mutation at the cell binding site were also performed (46,471).…”
Section: Disease Controlmentioning
confidence: 99%
“…These vaccines have proven useful in preventing the disease but present important constraints, such as the risk of virus escape from production plants and the difficulty in distinguishing infected animals from uninfected vaccinates. New vaccine strategies aimed at overcoming these problems have been developed, including subunit vaccines consisting of VP1 protein or chemically synthesized peptides (57,61), different DNA constructs expressing viral immunogens (6,8,15), and recombinant viruses (25,35,44,54,63). Live attenuated candidate vaccines for FMD lacking the leader L protease and mutations in the receptor binding sequence RGD have also been proposed (3,16 …”
Section: Discussionmentioning
confidence: 99%
“…To enhance the immune response induced by Ad5-O1C, we tested a vaccination regimen that included co-administration of pGM-CSF, a cytokine that has been shown to enhance the immune response of animals to some vaccines (Xiang & Ertl 1995, Lee et al 1998, Somasudaran et al 1999, Cedillo-Barrón et al 2001, Barouch et al 2002. We constructed an Ad5-pGMCSF virus that expressed biologically active pGM-CSF.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Cedillo- Barrón et al (2001) demonstrated that the addition of plasmid encoded pGM-CSF along with a DNA based FMDV empty capsid vaccine resulted in a statistically significant increase in the antibody levels against FMDV and somewhat improved the protection of vaccinated swine as compared to swine only given the empty capsid vaccine. However, in these studies the swine were challenged after 3 DNA inoculations and the increase in FMDV-specific antibody levels was only detected after the second inoculation.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation